A discourse analysis of Habakkuk - Fuller, David J. (Studia Semitica Neerlandica, 2020)
"Habakkuk is unique amongst the prophetic corpus for its interchange between YHWH and the prophet. Many open research questions exist regarding the identities of the antagonists throughout and the relationships amongst the different sections of the book. A Discourse Analysis of Habakkuk, David J. Fuller develops a model for discourse analysis of biblical Hebrew within the framework of Systemic Functional Linguistics. The analytical procedure is carried out on each pericope of the book separately, and then the respective results are compared in order to determine how the successive speeches function as responses to each other, and to better understand changes in the perspectives of the various speakers throughout"--